Territorializing Alternative Marketing Practices: - Viteri, Maria Laura (2024)
This work explores social and commercial alternative practices in a city located in a Pampean region heavily influenced by the agribusiness model. Its economy revolves around agriculture and livestock, relying heavily on external agricultural inputs for primary production. Using development anthropology and a sociology approach, this work positions the territorial space of the Agroecological Four Seasons Fair in Balcarce, in Buenos Aires, Argentina, as a generator of knowledge interfaces. This approach prioritizes the actors and their creative abilities in shaping courses of action and questions the idea that capital is the driving force. The focus is on the regeneration of socio-material resources from actors’ practices. Through the life stories and experiences of the actors, particularly the vendors, the aim is to understand the network of knowledge, including interactions with State institutional representatives. The consumers and the material aspects of the Four Seasons Fair represent various ways of life that are constantly evolving, undergoing processes of deterritorialization, influenced by residents from other cities. The fair is an expression of multiple ways of life that question existing models.